(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
In the article the results of syntaxonomical, cluster and ordinational analysis of segetal communities of the orchards, vineyards and sunflower’s fields of the Kherson region are given. Syntaxonomical scheme includes 6 associaions, 5 alliances, 2 orders of the class Stellarietea mediae.